Auto-oxidation promoted sp3 C–H arylation of glycine derivatives. Issue 27 (25th June 2018) - Wei, Yuanyuan; Wang, Jie; Wang, Yajun; Yao, Xiaoqiang; Yang, Caixia; Huo, Congde
Abstract : An auto-oxidation promoted sp 3 C–H arylation reaction between N -aryl glycine derivatives and electron-rich arenes, leading to the formation of N -aryl α-aryl α-amino acid derivatives, is described. This atom-economical and environmentally benign reaction proceeds smoothly under mild reaction conditions and requires only Brønsted acid and oxygen (balloon). A plausible radical involved mechanism is proposed. Abstract : An auto-oxidation promoted sp 3 C–H arylation reaction between N -aryl glycine derivatives and electron-rich arenes, leading to the formation of N -aryl α-aryl α-amino acid derivatives, is described. This atom-economical and environmentally benign reaction proceeds smoothly under mild reaction conditions and requires only Brønsted acid and oxygen (balloon). A plausible radical involved mechanism is proposed.